2005
DOI: 10.1080/15389580590931707
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Road Traffic Safety of the Mountain Areas in Southwest China Based on Wulong County, Chongqing Municipality

Abstract: Wulong County, one of the mountain counties in Southwest China, is now facing a complex and serious road traffic situation and serious traffic safety, with a high incidence of severe and very severe road traffic crashes. The crashes closely relate to imperfect road design, defective execution of traffic laws, imperfect management, and environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Over the past years, a great number of studies have concentrated on manifold factors influencing fatal and non-fatal road traffic accidents and their injury severity. Recent studies emphasized pre-crash human factors, such as alcohol consumption (Kim et al, 1995;Reynaud et al, 2002;Cummings et al, 2006;Yannis et al, 2008;Arranz and Gil, 2009;De Boni et al, 2013); seat-belt or Helmet usage (Cooper and Salzberg, 1993;Kim et al, 1995;Cummings et al, 2006); pre-crash vehicle factors such as the type of tyres (Strandoth et al, 2012;Elvik et al, 2013); at-crash vehicle factors such tire blow-outs, mechanical defects of the motor vehicles (Martin and Laumon, 2005;Barengo et al, 2006;Alam and Spainhour, 2009); pre-crash environmental factors such as roadway features or defects (Shankar et al, 1995;Karlaftis and Golias, 2002;Lee and Mannering, 2002;Chen and Chen, 2011;Kartal et al, 2011); at crash environmental factors such as road parameters, traffic signs, street lights, curbs or rumble strips (Hijar et al, 2000;Carson and Mannering, 2001;Zhou et al, 2005;Kim et al, 2007;Bombom and Edino, 2009;Šliupas, 2009;Pulugurtha and Bhatt, 2010;Jiang et al, 2011;Mamčic and Sivilevičius, 2013) using various statistical methods including logistic regression. In some researches, age (Cooper, 1990;Abdel-Aty et al, 1998;Zhang et al, 1998;Awadzi et al, 2008;Alam and Spainhour, 20...…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, a great number of studies have concentrated on manifold factors influencing fatal and non-fatal road traffic accidents and their injury severity. Recent studies emphasized pre-crash human factors, such as alcohol consumption (Kim et al, 1995;Reynaud et al, 2002;Cummings et al, 2006;Yannis et al, 2008;Arranz and Gil, 2009;De Boni et al, 2013); seat-belt or Helmet usage (Cooper and Salzberg, 1993;Kim et al, 1995;Cummings et al, 2006); pre-crash vehicle factors such as the type of tyres (Strandoth et al, 2012;Elvik et al, 2013); at-crash vehicle factors such tire blow-outs, mechanical defects of the motor vehicles (Martin and Laumon, 2005;Barengo et al, 2006;Alam and Spainhour, 2009); pre-crash environmental factors such as roadway features or defects (Shankar et al, 1995;Karlaftis and Golias, 2002;Lee and Mannering, 2002;Chen and Chen, 2011;Kartal et al, 2011); at crash environmental factors such as road parameters, traffic signs, street lights, curbs or rumble strips (Hijar et al, 2000;Carson and Mannering, 2001;Zhou et al, 2005;Kim et al, 2007;Bombom and Edino, 2009;Šliupas, 2009;Pulugurtha and Bhatt, 2010;Jiang et al, 2011;Mamčic and Sivilevičius, 2013) using various statistical methods including logistic regression. In some researches, age (Cooper, 1990;Abdel-Aty et al, 1998;Zhang et al, 1998;Awadzi et al, 2008;Alam and Spainhour, 20...…”
Section: Introductionmentioning
confidence: 99%
“…9 Ma et al 10 reviewed four nationallevel data sources used to estimate the burden of road traffic injuries, including mortality, injury, and crashes in China. Zhou et al 11 investigated road traffic safety in the mountain areas of Southwest China and suggested that the high incidence of severe crashes closely relates to imperfect road design, defective execution of traffic laws, imperfect management, and environmental factors. Wang et al 12 developed a driver safety approach behavioral model based on driver human factors analysis to prevent rear-end collisions in car-following situations.…”
Section: Introductionmentioning
confidence: 99%
“…More than 100 000 people die of traumatic injury and millions of people are injured each year in China. Furthermore, experts predict that the number of traumatic casualties will double in the 22nd century [14] . All these suggest that trauma in combination with cirrhosis is a challenge to Chinese doctors.…”
Section: Discussionmentioning
confidence: 99%